Jurnalisme Etis dan Transformatif: Tinjauan Akademik untuk Program Studi yang Distingtif - Baihaky, Rachmat; Rizal LK, Study (Faculty of Da'wa and Communications Sciences, 2025)
This research elaborates theoritical frame of “ethical and transformative journalism” as distinctive discipline and skills relevant to the School of Journalism at the Faculty of Da’wah and Communication (FDIKOM) UIN Syarif Hidayatullah Jakarta. Given to the ethical crisis within curent media culture, thus the urge to implement journalism skills on proselytization or da’wah (from Arabic da’a means to call) and empowerment, this research inclines to a qualitative approach by using descriptive analysis focusing on the academic foundation at the School of Journalism in current cyber era. This research confirms that journalism should not only concentrate on technical skills with its main orientation to economy and politial minded. By reformulating the discipline, the result of the study envisions the prinsiples of Islamic ethics, critical thinking, and transformation oirented. In so doing, the School of Journalism is projected pioneering the ethic-based journalism in the era of information disruption. Key words: journalism, ethics, tranformation, digital